Diet Quality, Saturated Fat and Metabolic Syndrome - Harrison, Stéphanie (Nutrients, 2020)
Indices reflecting overall diet quality are used globally in research to predict the risk of various diseases and metabolic disorders such as metabolic syndrome (MetS). Such indices are built to measure adherence to current dietary guidelines or to best assess the diet–disease relationship. Although mostly food-based, dietary guidelines often include recommendations to limit saturated fatty acid (SFA) intake in order to prevent cardiovascular diseases. However, not all diet quality indices consider SFA in their definition of diet quality. Additionally, the relationship between SFA consumption and the development of MetS remains unclear. The purpose of this short review was to explore the association between MetS and various diet quality indices and dietary patterns, with a focus on how SFA contributes to these associations.